Dos caras del secuetro (2008)
ABSTRACT: This article aims to apply the psychoanalytic thought to the kidnapping phenomenon both from the executant’s view and the victims’ view. The attempt to erase the subjectivity of both parts in order to reduce the victim to an exchange value and increase the kidnapping felony to an industry is clarified in this text. All of it kept within the bounds of the capitalist discourse, that which writes the contemporary times.